2016
DOI: 10.1007/978-3-319-18497-5_8
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Mediators of Remote Ischemic Conditioning: Important Role of eNOS/NO/Nitrite

Abstract: Remote ischemic conditioning (RIC) is a powerful cardioprotectant and neuroprotectant. The mechanism of protection likely involves circulating, blood-borne mediators that transmit the signal from the periphery to the brain. The neuroprotective effect of RIC may be partially related to improvements in cerebral blood flow (CBF). Nitrite is a key circulating mediator of RIC and may be a mediator of increased CBF and also mediate cytoprotection through its effects on nitrosylation of mitochondrial proteins such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…Subsequently, non-invasive applications of IC have been investigated and the benefits of RIC have been illuminated; that is, inducing ischemia in a healthy limb stimulates endogenous protective pathways (Iadecola and Anrather, 2011) that are transferable from one organ to another distant organ (Bøtker et al, 2010; Davies et al, 2013; Sloth et al, 2014). RIC involves the repetitive inflation and deflation of a BP cuff placed around a limb at pressures above SBP (Hess D. C. et al, 2016). …”
Section: Remote Limb Ischemia To Affect Distant Organsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, non-invasive applications of IC have been investigated and the benefits of RIC have been illuminated; that is, inducing ischemia in a healthy limb stimulates endogenous protective pathways (Iadecola and Anrather, 2011) that are transferable from one organ to another distant organ (Bøtker et al, 2010; Davies et al, 2013; Sloth et al, 2014). RIC involves the repetitive inflation and deflation of a BP cuff placed around a limb at pressures above SBP (Hess D. C. et al, 2016). …”
Section: Remote Limb Ischemia To Affect Distant Organsmentioning
confidence: 99%
“…Whilst the mechanisms involved in the remote signaling and in the stimulation of endogenous pathways to facilitate protective responses and structural changes in distant organs are not fully understood, evidence obtained through animal models and clinical trials supports a number of mechanisms involving; blood borne factors (Shimizu et al, 2009; Koch, 2010; Koch et al, 2014; Hess D. C. et al, 2016) induced by peripheral nerves (Jensen et al, 2012; Redington et al, 2012), epigenetic modulations of the genome (Stowell et al, 2010; Brand and Ratan, 2013; Thompson et al, 2015), and immune and anti-inflammatory responses (Konstantinov et al, 2004). Consequently, it is the interaction of blood borne and neuronal factors that are postulated to both initiate and transmit these signals to the brain.…”
Section: Remote Limb Ischemia To Affect Distant Organsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our pCASL measurement specifically assesses cortical blood flow(35). Although CASL depends for its calculation on “arterial transit time”(36, 37) -- a variable related mathematically to MFV -- its final output of cortical blood flow is influenced by distinct physiological variables such as cortical blood volume,(16) collateral patterns,(38) cortical network connectivity,(39) and local neurotransmitter effects(40, 41). Impaired cortical flow may thus have functional implications for the cortex that are distinct from the non-specific reduced flow velocity identified by TCD.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that NO is a reliable candidate in mediating the neuroprotective effects of ischemic postconditioning. Nitrite is a key circulating mediator of RIC and may be a mediator of increased CBF and cytoprotection via its effects on nitrosylation of mitochondrial proteins, such as complex I [47]. …”
Section: Neuroprotective Effects Of Ischemic Postconditioningmentioning
confidence: 99%